Alternative medicine - a replacement or an adjunctive for conventional therapy of chronic pain - Bobrzyk, Adrian; Kamińska, Weronika; Łyko, Grzegorz; Antos, Maria; Bator, Piotr; Wawryszuk, Angelika; Rumian, Maciej; Makowska, Weronika; Rachwał, Krystian (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Many people worldwide suffer from chronic pain. It is a very inconvenient condition on its own, not only an accompanying symptom of other diseases. Conventional drug treatment may be insufficient in some cases or may even cause serious side effects in the long term. In response to this, we aim to demonstrate the diversity of alternative pain management techniques in this review and identify conditions where such techniques may be beneficial to patients. State of knowledge: This paper evaluates some of the most common alternative pain management methods (acupuncture, massage, chiropractic, mind body therapies, herbal medicine, music therapy) and their application in specific cases of chronic pain. We also describe the possible mechanisms of action involved in the effectiveness of these techniques, based on contemporary studies. Summary: In conclusion, there are conditions where alternative medicine may be beneficial for patients suffering from chronic pain. The studies taken into account showed the best effects for chronic musculoskeletal pain treated with methods such as acupuncture and massage. Mind-body therapies may reduce stress levels and symptoms of depression associated with chronic pain, consequently improving the quality of patients' lives. However, alternative methods should not yet be considered as replacements for conventional drug therapy. More studies are needed to evaluate whether alternative therapies will play a significant role in chronic pain management in the future.